Synthesis, trypanocidal activity and molecular modeling studies of 2-alkylaminomethylquinoline derivatives - Muscia, Gisela Celeste (2011)
Research and development of new drugs effective in the treatment of Trypanosoma cruzi infections are a real need for the 16 million people infected in the Americas. In a previous work, a quinoline derivative substituted by a 2-piperidylmethyl moiety showed to be active against Chagas disease and was considered a lead compound for further optimization. A series of ten analogous derivatives were tested against epimastigotes as a first approach. In view of their promising results, six of them were evaluated against the blood and intracellular replicative forms of the parasite in humans. Among them, compound 12 which possesses a 6-acetamidohexylamino substituent showed remarkable improvement in activity against epimastigotes, trypomastigotes and amastigotes compared with the structure lead, as well as a good selectivity index for the two parasite stages present in humans. In addition, treatment of infected mice with compound 12 induced a significant reduction in parasitemia compared with non-treated mice. Molecular modeling studies were performed by computational methods in order to elucidate the factors determining these experimental bioactivities.